1999
DOI: 10.1177/019262339902700406
|View full text |Cite
|
Sign up to set email alerts
|

Contrast Medium- and Mannitol-Induced Apoptosis in Heart and Kidney of SHR Rats

Abstract: The induction of apoptosis by contrast media (CM) and mannitol (M)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 28 publications
1
32
0
Order By: Relevance
“…This interaction is evident in SHRs exposed to contrast. These SHRs show an acute worsening of cardiac damage (apoptosis and necrosis of cardiomyocytes) contributing to CI-AKI, as demonstrated by glomerular necrosis and sclerosis, tubular cell apoptosis and necrosis, interstitial lymphocytic infiltration, and apoptosis of endothelial cells and smooth muscle cells in small vessels of the heart and kidney [12,15] .…”
Section: Preexisting Cardiac and Renal Damage In The Shr Closely Resementioning
confidence: 99%
See 1 more Smart Citation
“…This interaction is evident in SHRs exposed to contrast. These SHRs show an acute worsening of cardiac damage (apoptosis and necrosis of cardiomyocytes) contributing to CI-AKI, as demonstrated by glomerular necrosis and sclerosis, tubular cell apoptosis and necrosis, interstitial lymphocytic infiltration, and apoptosis of endothelial cells and smooth muscle cells in small vessels of the heart and kidney [12,15] .…”
Section: Preexisting Cardiac and Renal Damage In The Shr Closely Resementioning
confidence: 99%
“…The aging male spontaneously hypertensive rat (SHR) has been used as a model for evaluating contrast-induced cardiac and renal toxicity [11][12][13][14][15][16] . We, therefore, hypothesize that in the aging male SHR, preexisting chronic heart failure and hypertension can mimic preclinical CRS in the clinical setting.…”
Section: Introductionmentioning
confidence: 99%
“…27 In adult SHR, acute osmotic stress induction by the administration of mannitol activates renal and cardiac apoptosis. 28 The precise involvement of osmotic stress in pathological conditions in this model and its potential role in human hypertension require more investigation.…”
Section: Other Extrinsic Factorsmentioning
confidence: 99%
“…In these regard, some studies have proposed that cytoplasmic proteolysis in cardiac cells is not always accompanied by nuclear fragmentation. 4,28 Thus, other tools beyond TUNEL should be applied for the evaluation of cardiomyocyte apoptosis.…”
Section: Pathophysiological Significancementioning
confidence: 99%
“…Moreover, our previous study showed that male SHR were more susceptible than WKY rats to the cardiotoxicity of radiocontrasts and the contrast mediums-induced toxicity was associated with apoptosis (Zhang et al, 1999). We reasoned that male SHR could be a suitable animal model for accelerating and amplifying SK&F 95654-induced cardiovascular injury and associated biomarker responses.…”
Section: Introductionmentioning
confidence: 99%